Integration of Value Engineering for Design for Assembly in Product Design: A Comprehensive of Literature Review - Hartanto, Adrian; Ginting, Rosnani; Ishak, Aulia (TALENTA Publisher, 2024)
This study explains the benefits obtained from the integration of Design for Assembly (DFA) and Value Engineering (VE) methods in the product design process. DFA is proven to provide benefits such as product simplification, reduced assembly costs, and improved quality by creating product structures that are simpler and easier to install. While VE adds value by taking into account the replacement of expensive or difficult-to-assemble components, speeding up overall assembly time. Although specific research on the integration of these two methods may be limited, studies show that the combination of DFA and VE produces design alternatives that consider various aspects of the product life cycle. The result is reduced costs, faster development times, and a reduced need for rework. The concepts and benefits of integrative DFA and VE approach can be an effective strategy for enhancing assembly efficiency and reducing production costs in product design.